Status Hukum Tanah Bekas Hak Guna Bangunan yang Tidak Diperpanjang dalam Perspektif Pemanfaatan Aset Negara (Studi Kasus Lahan Pelabuhan Sofifi) - Risky Herduiva Pradana; Husen Alting; Siti Barora Sinay (LPPM Institut Pendidikan Nusantara Global, 2026)
This research aims to analyze the control of former Building Use Right (Hak Guna Bangunan/HGB) land owned by PT. Darko Modul & Timber whose term has expired and was not extended according to the Indonesian land law framework, as well as to examine the legal construction required to provide legal certainty over the status of such land so that it may be utilized as a State Asset (State-Owned Property), with a case study of the Sofifi Port land. This research employs an empirical legal research method with a qualitative approach. Empirical legal research is conducted to examine the implementation of law in practice (law in action) by analyzing how land law regulations and state asset management norms are applied in reality. The data used in this research consist of primary data obtained through interviews with relevant stakeholders and secondary data derived from laws and regulations, court decisions, legal doctrines, and related legal literature. The results of this research indicate that the expiration of the Building Use Right without extension results in the termination of the right by operation of law, and consequently, the land reverts to land directly controlled by the state. This legal consequence is further affirmed by the Decision of the Soasio District Court Number 16/Pdt.G/2025/PN Sos, which declares that the rights of PT. Darko Modul & Timber over the disputed land have been extinguished and that the former Building Use Right Land Number 01 of 1985 constitutes state land. However, although the court decision has provided normative and judicial legal certainty, legal certainty from the perspective of land administration law has not yet been fully realized, as it has not been followed by administrative actions in the form of state land designation and registration of the land as State-Owned Property. Therefore, an integrative legal construction through land administration and state asset management mechanisms is required to ensure that the utilization of the land for public purposes, particularly as the Sofifi Port, is supported by clear legal status and provides legal protection for all parties involved.